2013
DOI: 10.2340/16501977-1109
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of gait kinematics and walking ability of people with multiple sclerosis who are new users of functional electrical stimulation

Abstract: The acute application of functional electrical stimulation resulted in an orthotic effect through a change in ankle and knee kinematics and increased walking speed over a short distance in people with multiple sclerosis who experience foot drop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…When FES is used for the first time these effects have been termed an 'initial orthotic effect" of the stimulation [28]. Recent evidence shows the initial orthotic effects of FES on the gait of people with MS extend to improvements in the overall kinematic pattern of lower limbs during gait [27,29], including increased ankle dorsiflexion during swing [29,30], and at initial foot contact [29][30][31] leading to increases in stride length [29,32]. The maintenance of an orthotic effect with prolonged use of FES has been referred to as a 'continuing orthotic effect' [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When FES is used for the first time these effects have been termed an 'initial orthotic effect" of the stimulation [28]. Recent evidence shows the initial orthotic effects of FES on the gait of people with MS extend to improvements in the overall kinematic pattern of lower limbs during gait [27,29], including increased ankle dorsiflexion during swing [29,30], and at initial foot contact [29][30][31] leading to increases in stride length [29,32]. The maintenance of an orthotic effect with prolonged use of FES has been referred to as a 'continuing orthotic effect' [28].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increased interest in the effects of FES on gait in MS [29,30,32], no studies to date have investigated the initial orthotic effect of FES on fatigue induced changes in gait that occur in people with MS [18]. Additionally it remains unclear whether prolonged use of FES delivers continuing orthotic effects and therapeutic effects (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…They reduced the time to 3 minutes, but acknowledged that the validity and reliability of the 3-minute walk test were not established. 22 Recently, Scott et al 5 reported no benefit even on the 6MWT with acute application of FES in 12 pwMS who had no prior exposure to FES. Compared with prior research, the participants in this study were not habitual users of FES, postulating that an extended period of FES use might be needed to observe a clinically significant difference in mobility.…”
Section: Functional Electrical Stimulation On Gait Effects Gait Speedmentioning
confidence: 99%
“…Compared with prior research, the participants in this study were not habitual users of FES, postulating that an extended period of FES use might be needed to observe a clinically significant difference in mobility. 5 Overall, a majority of the studies observing the effects on walking performance have reported orthotic effects, [4][5][6][7][8][9]13,14,16,20,22,24 and in some cases a total orthotic benefit after weeks of FES device use 8,24 with one study noticing this benefit only after 2 weeks. 16 Training effects have been consistently reproduced in nonprogressive neurologic conditions, such as stroke and spinal cord injury populations.…”
Section: Functional Electrical Stimulation On Gait Effects Gait Speedmentioning
confidence: 99%
See 1 more Smart Citation